Visual Evoked potential signal processing and analysis for normal and galucomic eyes - Abdelkader, Hamed Ibrahem; Abdelkader, Mona; Kabeel, Mohammed; alya, malak (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Visual evoked potentials (VEPS) are obtained from optic tract by recording the evoked potentials generated by retinal stimulation. The flash VEP (FVEP) is used less frequently than pattern reversal VEP (PRVEP) because; it shows great variation in both latency and amplitude. The present study was undertaken to evaluate the effect of change of wavelength of flash and change of check size on the parameters of visual evoked potential (amplitude and latency) in normal individuals and glaucoma patients. The group of healthy subjects in the age of 20-45 years while the group of glaucoma subjects where in the age of 25-50 years. The two groups were exposed to flash VEP with white light and blue color and they also were exposed to checks subtending a visual angles of 15, 30,60 and 120 minutes of arc. The measured data were statistically analyzed and summarized by histograms. The interindividual and intraindividual in latencies and amplitudes for FVEP were assessed using the coefficient of variation (COV). In conclusion, monochromatic flash VEP was preferred than white as there were minimal inter and intra individual variation of latencies and amplitudes. The most preferred check size in PRVEP was 120' for the two groups.